2012
DOI: 10.1002/jid.2838
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the First Job in a Slack Labour Market: Job Matching in South Africa

Abstract: Little is known about job matching in labour markets with mass unemployment. Using a unique data set of labour market experiences of young African job participants in South Africa, our findings show that accessing jobs through various employment channels is non‐random. Specifically, different individual, household, job and firm characteristics are correlated with the probability of accessing the first job via a particular channel, indicating that firms and/or job seekers select themselves into the use of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…The results obtained in the present paper agree with what Schöer et al (2014) or Sin and Amaral (2017) pointed out regarding the fact that the probability of being hired increases as does the company's size. As for the other variables, we cannot compare this to other studies as they have not been analyzed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in the present paper agree with what Schöer et al (2014) or Sin and Amaral (2017) pointed out regarding the fact that the probability of being hired increases as does the company's size. As for the other variables, we cannot compare this to other studies as they have not been analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…Brown and Hesketh (2004) showed that the importance given to university degrees by employers has decreased, whereas the importance they give to personal characteristics and people's skills has increased. Still, we should note it is not only about knowledge and personal skills, but also to what degree they fit the employer's requirements (Schöer et al 2014). There are few papers trying to study this relationship, but they do not actually study the employer's viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…An extremely high rate of youth unemployment in South Africa has been and is still an increasingly pressing issue (Mlatsheni and Rospabé, 2002;Rankin and Roberts, 2011;Schöer et al, 2012). Unemployed youths may be vulnerable to psychological and financial stress as well to feelings of hopelessness, which are likely to increase the risk of suicide among these groups.…”
Section: Resultsmentioning
confidence: 99%
“…The limited information content of education qualifications is consistent with the large role of referrals in hiring: more than half of all firms report that referrals are their preferred recruitment mechanism(Schöer et al, 2014).8 Small firms report an average of two dispute resolution cases in the previous year, requiring an average of 11 days of staff time per case(Rankin et al, 2012).9 Only 18% of SME owners know the conditions that made a contract valid or rules governing severance pay(Bertrand and Crépon, 2019).…”
mentioning
confidence: 83%